EFFECTIVENESS OF DIRECT OBSERVATION OF PROCEDURAL SKILLS (DOPS) AS AN ASSESSMENT TOOL IN SURGERY: Direct Observation of Procedural Skills - Khaliq, Tanwir (Pakistan Armed Forces Medical Journal, 2014)
The introduction of the Modernising Medical Careers (MMC) program in England has produced a shift towards a competency based system for training and assessment in postgraduate medical education in the UK and rest of the world1. This change also influenced post garduate training in Pakistan and the College of Physicains and Surgeons also shifted to competence based post graduate curriculum. Introduced as part of a new curriculum in April 2005, it was designed to be a groundbreaking world-leading programme providing graduates with a broader exposure to medical practice and specialist training. To meet this challenge the curriculum identified a range of competencies that had never been met before including communication skills, leadership and teamwork2.